Pemberdayaan Pengrajin Songket Bali Utara - I Made Pradana Adiputra; Ketut Nala Hari Wardana (FEB-UP Press, 2020)
Jinengdalem Village is one of the villages producing songket weaving crafts mainly with raw materials of silk thread besides gold thread. The limitation of the craftsmen in producing songket is because it is done by consumer orders, and there is no unified business in a joint business group of songket artisans. The community service activities of the IbM also increase songket production with the effective use of cag-cag looms as traditional tools which until now have not been able to be replaced as songket producers because of the anatomical guidelines of the craftsman's body at work and can produce songket cloth with good quality. Community service activities include the establishment of KUBE as the basis for the formation of songket cooperatives, the development of North Bali typical songket designs, the natural coloring of plant material from flowers, fruit, roots and plant skins and the effective use of traditional cag-cag tools. Through the method of socialization, training and mentoring of the Jinketdalem village songket craftsmen, targets and outcomes were produced: the formation of KUBE, natural dyeing silk threads as the base material of songket, songket productivity with cag-cag looms and more diversified motif designs in accordance with North Bali (Buleleng).